Chemical composition, sources and evolution processes of aerosol at an urban site in Yangtze River Delta, China during wintertime. (December 2015) - Zhang, Yunjiang; Tang, Lili; Yu, Hongxia; Wang, Zhuang; Sun, Yele; Qin, Wei; Chen, Wentai; Chen, Changhong; Ding, Aijun; Wu, Jing; Ge, Shun; Chen, Cheng; et al.
Abstract: To investigate the composition, sources and evolution processes of submicron aerosol during wintertime, a field experiment was conducted during December 1–31, 2013 in urban Nanjing, a megacity in Yangtze River Delta of China. Non-refractory submicron aerosol (NR-PM1 ) species were measured with an Aerodyne Aerosol Chemical Speciation Monitor. NR-PM1 is dominated by secondary inorganic aerosol (55%) and organic aerosol (OA, 42%) during haze periods. Six OA components were identified by positive matrix factorization of the OA mass spectra. The hydrocarbon-like OA and cooking-related OA represent the local traffic and cooking sources, respectively. A highly oxidized factor related to biomass burning OA accounted for 15% of the total OA mass during haze periods. Three types of oxygenated OA (OOA), i.e., a less-oxidized OOA (LO-OOA), a more-oxidized OOA (MO-OOA), and a low-volatility OOA (LV-OOA), were identified. LO-OOA is likely associated with fresh urban secondary OA. MO-OOA likely represents photochemical products showing a similar diurnal cycle to nitrate with a pronounced noon peak. LV-OOA appears to be a more oxidized factor with a pronounced noon peak. The OA composition is dominated by secondary species, especially during haze events. LO-OOA, MO-OOA and LV-OOA on average account for 11%, (18%), 24% (21%) and 23% (18%) of the total OA mass for the haze (clean) periods respectively. Analysis of meteorological influence suggested that regional transport from the northern and southeastern areas of the city is responsible for large secondary and low-volatility aerosol formation. Highlights: ACSM measurement was conducted during wintertime in YRD. Secondary inorganics dominate the PM1 pollution in haze periods. SOA and aged BBOA significantly contribute to organics in hazy day. Secondary low-volatility production was extremely affected by regional transport.